The Relevance of Comprehensive Profit Value of Islamic Entities in Indonesia and Malaysia - Wahyudi, Moch.; Kusuma, Marhaendra; Ahamad, Abdul Hadi Bin (Fakultas Ekonomi Universitas Kadiri, 2025)
Fundamental changes in the structure of income statement reporting do not only occur in conventional entities, but also in sharia entities. These changes are the presence of comprehensive income information, reclassification of other comprehensive income (OCI) components and the interests of non-controlling shareholders. This study aims to test the reaction of the sharia market to these three pieces of information in financial reporting. Research data on sharia entities listed on the Jakarta Islamic Index (JII) and Kuala Lumpur Composite Index (KLCI) with a sample of 30 companies, for the period 2013 - 2023, observation data 564. Hypothesis testing with moderated regression analysis (MRA). The results of the study indicate that the Indonesian and Malaysian markets as representatives of the largest sharia emerging markets in Southeast Asia respond to comprehensive income information from sharia entities. The presentation of reclassification of OCI components and the interests of non-controlling shareholders strengthens the content of comprehensive income information. Further analysis with different proxy measurements of value relevance variables, stock returns and natural logarithms of stock prices, both provide the same test results. Likewise, disaggregated data based on country of origin, namely Indonesia and Malaysia, and financial subsectors, namely Islamic banking and non-banking entities, also provide similar results. The originality of this study is the examination of the moderating role of reclassification of OCI components and non-controlling interests of emerging market Islamic entities in the influence of comprehensive income and stock returns